Does enrolment in single-sex schools affect marriage outcomes? - Chua, Kah Beng (2019)
Low fertility rates in Singapore will reduce the labour force size and impede economic growth. Apart from encouraging more children, government interventions should focus on promoting marriage since families are the building blocks of society. This paper investigates whether different types of schooling affects marriage outcomes, specifically, whether individuals from single-sex schools spend more time searching for partners and have a lower probability of getting married. Using logistic regression models, we find that individuals from single-sex schools on average spend 14.3 months longer to search for partners and are 0.37 times as likely to get married compared to those from mixed schools, ceteris paribus. Individuals who plan to have more children and couples who prefer each specialising in either work or home production are also found to be more likely to get married. Robustness checks using other specifications and model reveal similar results. One other interesting finding is that individuals who enrolled in single-sex secondary schools have lower probability of getting married as opposed to those from single-sex primary schools. These results have many policy implications for the Singapore Government to examine so as to promote marriage and subsequently improve fertility rates.